2019
DOI: 10.1088/1475-7516/2019/04/050
|View full text |Cite
|
Sign up to set email alerts
|

The relativistic dipole and gravitational redshift on LSS

Abstract: We compute the dipole of the galaxy correlation function at 1-loop in perturbation theory by including all the relevant relativistic contributions. This provides a description and understanding of what the dipole truly measures, in particular in relation to the gravitational redshift effect in Large Scale Structure. In order to develop this perturbative approach we have computed for the first time the relevant relativistic corrections to third order in perturbation theory, including the corresponding non-linea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 91 publications
(280 reference statements)
1
39
0
Order By: Relevance
“…Here v is the peculiar velocity, Φ is the gravitational potential, H is the comoving Hubble parameter and r is the line-of-sight comoving distance. At second order, it is shown in [9] that (see also [12])…”
Section: Introductionmentioning
confidence: 98%
“…Here v is the peculiar velocity, Φ is the gravitational potential, H is the comoving Hubble parameter and r is the line-of-sight comoving distance. At second order, it is shown in [9] that (see also [12])…”
Section: Introductionmentioning
confidence: 98%
“…Nevertheless, as shown in Breton et al (2019), the deviation from linear theory appears manifest when we con-sider the relativistic contributions. In particular, the relativistic contributions tend to have a large impact on nonlinear correction (see Di Dio & Seljak 2019, for a quantitative study with perturbation theory), and a large deviation is indeed found for the dipole purely arising from relativistic effects below 40 − 50 h −1 Mpc. In this respect, quasi-linear treatment of wide-angle effects still deserves further investigation.…”
Section: Comparison With Simulationsmentioning
confidence: 98%
“…[25][26][27] for second and Refs. [28][29][30] for third orders). At linear order, the gauge-invariant relativistic number counts read as follows (by following the notation of Refs.…”
Section: Relativistic Effects In the Lyα-quasar Cross-correlation Funmentioning
confidence: 99%